(untitled) (African Journal of Science, Technology and Social Sciences, 2025)
In the rapidly evolving landscape of higher education, universities are increasingly recognized not just as centers of learning, and research, but as dynamic knowledge intensive organizations. Their core mission to create, disseminate and apply knowledge fundamentally relies on the continuous and effective exchange of information, insights and expertise among faculty, administrative staff and researchers. The objective of the study was to assess the influence of job characteristics on knowledge sharing with management support as a moderating variable in Chartered Universities in Kenya. A cross-sectional research design was adopted and the target population of the study was 384. Data was collected through a self-designed questionnaire. To determine the ideal sample size, Slovins’formula, was used to arrive at a sample size of 196 managers. Pilot test was done to test the validity of data instrument in six universities that were randomly sampled. The questionnaire was validated by use of Cronbach’s Alpha for Content validity and panel of expert’s reviews to ensure reliability and consistency of results when applied repeatedly under similar conditions. Inferential statistics results showed strong R2 while the results of ANOVA for the regression model showed an F statistic that was within the predictable range. The data was tested for adherence to the assumptions of multiple linear regression and the results indicated that the study complied with the definitive tests of normality, autocorrelation and multicollinearity. The results showed a positive significance correlation between job characteristics on knowledge sharing in chartered universities in Kenya since (P< 0.05). The study recommends the university management to strategically formulate job characteristic policies that boast knowledge sharing as well as help employees understand how their roles and competencies help promote knowledge sharing. The study also recommends clear policies on designing jobs whose task significance, job autonomy and job feedback enhances Knowledge sharing among the university teaching and non-teaching staff. Human resource department should also provide precise guidelines and explicitly integrate knowledge sharing attributes into job description and job specification. The study has implications on theory, empirical and practical contributions to this body of knowledge.